Valuing financial, health, and environmental benefits of Bt cotton in Pakistan. (18th February 2013) - Kouser, Shahzad; Qaim, Matin
Abstract Data from a farm survey and choice experiment are used to value the benefits of Bt cotton in Pakistan. Unlike previous research on the economic impacts of Bt, which mostly concentrated on financial benefits in terms of gross margins, we also quantify and monetize health and environmental benefits associated with technology adoption. Due to lower chemical pesticide use on Bt cotton plots, there are significant health advantages in terms of fewer incidents of acute pesticide poisoning, and environmental advantages in terms of higher farmland biodiversity and lower soil and groundwater contamination. Farmers themselves value these positive effects at US$ 79 per acre, of which half is attributable to health and the other half to environmental improvements. Adding average gross margin gains of US$ 204 results in aggregate benefits of US$ 283 per acre, or US$ 1.8 billion for the total Bt cotton area in Pakistan.